Mechanism of DOPA radical generation and transfer in metal-free class Ie ribonucleotide reductase based on density functional theory - Jinxin Zou; Yao Chen; Wei Feng (Computational and Structural Biotechnology Journal, 2022)
Quantum mechanical/molecular mechanical (QM/MM) calculations were carried out to investigate the mechanisms of the generation, transfer, and regeneration of the DOPA radical for metal-free class Ie ribonucleotide reductase. The crystal structure of MfR2 (Nature, 2018, 563, 416–420) was adopted for the calculations. The QM/MM calculations have revealed several key points that are vital for understanding the mechanisms. The superoxide O2·− provided by the flavoprotein NrdI cannot directly oxidize the residue Tyr126 to the DOPA radical. It should be protonated to HO2·. The calculation results suggest that the covalent modification of Tyr126 and the DOPA radical generation can be carried out with no involvement of metal cofactors. This addresses the concerns of the articles (Nature, 2018, 563, 416–420; PNAS, 2018, 115, 10022–10027). Another concern from the articles is that how the DOPA radical is transferred from the radical trap. The DFT calculations have demonstrated that Lys213 is a key residue for the radical transfer from the DOPA radical. The ε-amino group of Lys213 is used not only as a bridge for the electron transfer but also as a proton donor. It can provide a proton to DOPA126 via a water molecule, and thus the radical transfer from DOPA126 to Trp52 is facilitated. It has also been revealed that the protonation of Asp88 is the prerequisite for the DOPA radical generation and the radical transfer in class Ie. Once the radical is quenched, it can be regenerated via the oxidations by superoxide O2·− and hydroperoxyl radical HO2·.